Influence of σ₁ − σ₂ stress on phase transition and physical properties of KD₂PO₄-type ferroelectrics - Stasyuk, I.V.; Levitskii, R.R.; Zachek, I.R.; Duda, A.S. (Condensed Matter Physics, 2001)
Within the proposed earlier model we study effects of stress σ₁ − σ₂ on the
KD₂PO₄ type ferroelectrics. In the cluster approximation for the short-range
correlations, we calculate dielectric, piezoelectric, and elastic characteristics
of a strained by σ₁ −σ₂ KD₂PO₄ type crystal. Numerical analysis of the
obtained results is performed. Stress dependences of the calculated characteristics
and the phase diagram are explored. Possibility of the induced
by σ₁ − σ₂ phase transition into a new paraelectric phase with monoclinic
symmetry is discussed На основі запропонованої раніше моделі вивчається вплив напруги
σ₁ − σ₂ на сегнетоелектрики типу KD₂PO₄. В кластерному наближенні з врахуванням короткосяжних і далекосяжних взаємодій розраховано і досліджено пружні, діелектричні і п’єзоелектричні характеристики KD₂PO₄, проведено детальний числовий аналіз отриманих результатів. Досліджено температурні і баричні залежності розрахованих характеристик. Вивчаються індуковані напругою σ₁ − σ₂ фазові
переходи.